Visionary Leadership and Corporate Culture for Increasing Competitiveness and Customer Interest toward Transformative Islamic Education - Darmawan, Luqi; Sujianto, Agus Eko; Sulistyorini, Sulistyorini (Journal of Modern Islamic Studies and Civilization, 2025)
Visionary leadership and corporate culture have an important role in increasing competitiveness and customer interest. This study aims to describe visionary leadership and corporate culture in increasing the competitiveness and interest of customers of transformational Islamic education. This research method uses a qualitative descriptive approach in the form of a literature review (library research). The analysis technique used is content analysis. The results of the study on visionary leadership and corporate culture in increasing competitiveness and customer interest in this transformative education found: 1) Efforts to increase customer interest require the accuracy of the leader's vision regarding the characteristics of the interests and satisfaction of the targeted or expected customers and educational program models that are in line with it and the existence of benchmarks for service standards that are in demand by customers and are realized in the service programs offered, both in terms of reliability, sensitivity, certainty, empathy and its form, 2) Customer interest is also influenced by the leader's vision in winning the competitiveness through a low-cost approach, service differentiation, focusing on strengthening competition in the same service program, or a diversification approach, 3) Efforts to increase competitiveness and customer interest must be built on the basis of an ideal and progressive organizational culture by prioritizing the principle that culture is not just regulations, in accordance with the conditions and movement of the institution's progress, in accordance with the challenges faced by the institution, can be followed by all members and truly implemented by all members.